Os influenciadores digitais e a compra online dos seus seguidores - Carvalho, Rui dos Santos (2022)
Due to the permanent development of information and communication technologies (ICT) and the evolution of the internet, we witness constant developments on a daily basis. As a result, thanks to these developments, platforms such as social networks and e- Commerce have started to gain more visibility and an important and assiduous role among their users. In this context, social networks are currently seen as an important stage where their users can produce and share content with their interest groups, thus expressing their opinions and contributing to the exchange of information with others. With the evolution of the Internet, there was a transfer from the traditional medium to the digital medium, as is the case, for example, of the Electronic Word of Mouth (eWOM), which translates into a powerful tool with the ability to positively or negatively influence the purchase intention of its followers. In this scenario, companies have been forced to keep up with the persistent changes in the market, as well as the needs of their customers. In this context, digital influencers are seen as potential individuals who contribute to the satisfaction of their customers' needs by sharing information. To this assertion, we can add the trust and credibility of digital influencers, fundamental dimensions in decision making in the purchase intention of their followers. Given this context, this research aims to study the role of digital influencers in the online purchase decision making of their followers. In order to obtain and analyze the data, we used a quantitative methodology, through a questionnaire survey. The results obtained allow us to conclude that digital influencers have a preponderant role in the online purchase intention of their followers.